Jung's concept of the mother archetype and its influence on women's lives : a literature review - Vermaak, Janneke; Jung, C. G.(Carl Gustav),1875-1961 (Stellenbosch : Stellenbosch University, 2012)
Thesis (M Ed) -- University of Stellenbosch, 1998.